Effect of Hydroxychloroquine on the Retinal Layers: A Quantitative Evaluation with Spectral-Domain Optical Coherence Tomography - Hasim Uslu; Bulent Gurler; Aydin Yildirim; Mehmet Gurkan Tatar; Feride Aylin Kantarcı; Hasan Goker; Hatice Seval Pehlevan; Hatice Nur Colak (Journal of Ophthalmology)
Purpose. To evaluate the effect of hydroxychloroquine on retinal pigment epithelium- (RPE-) Bruch’s membrane complex, photoreceptor outer segment, and macular ganglion cell-inner plexiform layer (GCIPL) thicknesses using spectral-domain optical coherence tomography (SD-OCT). Methods. In this prospective case-control study, 51 eyes of 51 hydroxychloroquine patients and 30 eyes of 30 healthy subjects were included. High-quality images were obtained using a Cirrus HD-OCT with 5-line raster mode; the photoreceptor inner segment (IS) and outer segment (OS), sum of the segments (IS + OS), and RPE-Bruch’s membrane complex were analyzed. Results. The thicknesses of the IS + OS and OS layers were significantly lower in the hydroxychloroquine subjects compared to the control subjects (P<0.05). RPE-Bruch’s membrane complex thicknesses were significantly higher in the hydroxychloroquine subjects than for those of the control subjects (P<0.05). The minimum and temporal-inferior macular GCIPL thicknesses were significantly different between the patients with hydroxychloroquine use and the control subjects (P=0.04 and P=0.03, resp.). Conclusions. The foveal photoreceptor OS thinning, loss of GCIPL, and RPE-Bruch’s membrane thickening were detected in patients with hydroxychloroquine therapy. This quantitative approach using SD-OCT images may have important implications to use as an early indicator of retinal toxicity without any visible signs of hydroxychloroquine retinopathy.